Risk factors for sexual pain among physically active women (2020)
Introduction: Sexual pain is common among women but little is known about associations with exercise and physical activity. Aim: To determine the prevalence of sexual pain among physically active women and to evaluate cycling and other potential risk factors. Methods: This is a secondary data analysis of a study on the urinary and sexual wellness of physically active women recruited through sporting clubs and targeted social media advertising. We used multivariable logistic regression to assess the role of cycling and exercise in reporting any, frequent, or severe sexual pain, controlling for demographic, relationship, and health risk factors. Main outcome measure: Sexual pain, including frequency and severity, was measured using the Female Sexual Function Index. Results: A total of 2,039 women were included, with 1,097 (54%) reporting any level of sexual pain, 364 (18%) experiencing frequent pain, and 378 (19%) reporting severe pain. Less than 5% of women reported diabetes or hypertension, and the cohort had a median body mass index of 23.3 (interquartile range 21.4–25.7). Increasing age and body mass index were protective against any sexual pain, as was cycling (odds ratio [OR] 0.73 [95% CI 0.59–0.90]). Participants who reported being “moderately satisfied” (OR 0.53 [95% CI 0.31–0.91]) or “very satisfied” (OR 0.33 [95% CI 0.19–0.56]) with their emotional closeness to a sexual partner had decreased odds of any sexual pain. Conclusion: Experiencing any sexual pain is common in physically active women, with a prevalence of over 50%; however, weekly energy expenditure from exercise was not associated with sexual pain. Cycling participation and higher levels of emotional closeness and intimacy were associated with less pain. Patients between the ages of 18 and 30 years who were normal or underweight incurred the highest risk of sexual pain.